Clinical value of prenatal MRI for diagnosis of isolated ventriculomegaly and prediction of early postnatal developmental outcomes. (13th January 2019) - Li, Zhi; Lv, Yidan; He, Pingya; Luo, Zhiqin; Pan, Liming; Du, Ying; Fang, Rong; Liu, Yuqin; Li, Lan; Zhu, Ling
Abstract: Objective: To investigate the relationship of ventriculomegaly (VM) with postnatal neurological development. Methods: Fetuses with isolated VM on MRI ( n  = 160; VM group) were separated into three subgroups according to lateral ventricle width: subgroup A (10.0‐12.0 mm; n  = 113), subgroup B (12.1‐15.0 mm; n  = 37), and subgroup C (>15.0 mm; n  = 10). Fifty normal fetuses formed a control group. Post‐delivery changes in ventricular width and neurological development were assessed with MRI/ultrasonography and the Gesell Development Schedules (GDS), respectively, at 3, 6, 12, and 18 months. Results: GDS scores of subgroup A and subgroup B did not differ from that of the controls at 3 and 6 months. Subgroup B scores differed significantly from the control scores at 12 and 18 months. Subgroup C scores differed from the control scores at all‐time points (all P  < 0.05). In the VM group, GDS scores at 12 and 18 months were significantly different from the scores at 3 months, and the score at 18 months was significantly different from the score at 6 months ( P  < 0.05 for all). Conclusion: The milder the VM, the more likely it was to disappear or improve in the postnatal period. However, specific postnatal rehabilitation should be considered when fetal ventricular width is greater than 12.1 mm. Abstract : What is already known about this topic? The degree of ventriculomegaly is associated with developmental outcomes. What does this study add? Prenatal MRI diagnosis of isolated ventriculomegaly can help identify infants in whom developmental delays are likely.